Meaningful Use of a Standardized Terminology to Support the Electronic Health Record in New Zealand - Monsen, K.; Honey, M.; Wilson, S. (Applied Clinical Informatics, 2010)
Meaningful use is a multidimensional concept that incorporates complex processes; workflow; interoperability; decision support; performance evaluation; and quality improvement. Meaningful use is congruent with the overall vision for information management in New Zealand. Health practitioners interface with patient information at many levels, and are pivotal to meaningful use at the interface between service providers, patients, and the electronic health record. Advancing towards meaningful use depends on implementing a meaningful interface terminology within the electronic health record. The Omaha System is an interface terminology that is integrated within Systematized Nomenclature of Medicine – Clinical Terms (SNOMED CT®), and has the capacity to disseminate and capture information at the point of care because its codes are simple defined terms. Two community nursing and allied health providers who are considering using the Omaha System in clinical systems for gathering intervention and outcomes data within the personal EHR include Nurse Maude and the Royal New Zealand Plunket Society. Help4U is investigating using the Omaha System as a way to standardise health terminology for consumer use. The Omaha System is also a good fit with the Midwifery and Maternity Providers Organisation (MMPO) existing clinical information system to describe and capture data about interventions currently recorded as free text. As a country that promotes access to affordable primary care and free hospital care, within an environment constrained by resource limitations, maximizing the use of data is key to demonstrating health outcomes for the population.
Keywords: Electronic health records and systems; clinical documentation and communication; clinical data management; standards; evaluation